Value-based modulations in human visual cortex - Serences, John T. (2008)
Economists and cognitive psychologists have long known that prior rewards bias decision making in favor of options with high expected value. Accordingly, value modulates the activity of sensorimotor neurons involved in initiating movements towards one of two competing decision alternatives. However, little is known about how value influences the acquisition and representation of incoming sensory information, or about the neural mechanisms that track the relative value of each available stimulus to guide behavior. Here, fMRI revealed value-related modulations throughout spatially selective areas of the human visual system in the absence of overt saccadic responses (including in V1). These modulations are primarily associated with the reward history of each stimulus and not to self-reported estimates of stimulus value. Finally, subregions of frontal and parietal cortex represent the differential value of competing alternatives and may provide signals to bias spatially-selective visual areas in favor of more valuable stimuli.